Morphological, physicochemical, and phytochemical characterization of Camellia dormoyana (Pierre) Sealy from Vietnam - DOAN THANH LUAN; TRAN VAN CHEN; DANH DUC NGUYEN; QUANG CUONG TRUONG; KHUONG HUU THANG; NGUYEN THANH TO NHI; VO NGOC LINH GIANG; NGUYEN XUAN SANG; NGUYEN THANH TRIET (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Luan DT, Chen TV, Nguyen DD, Truong QC, Thang KH, Nhi NTT, Giang VNL, Sang NX, Triet NT. 2022. Morphological, physicochemical, and phytochemical characterization of Camellia dormoyana (Pierre) Sealy from Vietnam. Biodiversitas 23: 5869-5883. Camellia dormoyana (Pierre) Sealy has been used as a flavor, beverage, and folk medicine. Micromorphological features, physicochemical, and phytochemical aspects of C. Dormoyana have not been reported. Thus, further research is necessary to accurately verify the plants and determine their quality and safety for raw materials. This study aimed to characterize morphological, physicochemical, and phytochemical aspects of C. dormoyana from Vietnam. The results present that the species is easily distinguished macromorphologically by the superior ovary, 5-or 6-carpellate, glabrous, and styles glabrous, 5-or 6-parted, and uniformly fused. Micromorphologically, the structure of leaves and stems have similarities between the investigated species in the genus Camellia. Cork-wart, anisotricytic stoma, and stomatal clusters were found in the lower epidermis surface of leaves. The common presence of calcium oxalate crystals and sclereid cells was observed in the stem and the petiole. All epidermis fragments, parenchymal fragments, starch granules, calcium oxalate crystals, sclereid cells, spiral vessels, and red-brown oleoresin masses are standard components present in leaf powder. The physicochemical parameters of leaf powders all meet acceptable standards. The phytochemical compositions of the leaf extract contain lipids, carotenoids, essential oil, reducing compounds, amino acids, triterpenoids, saponins, tannins, and flavonoids.